A Critique of Religious Pedagogy and the Possibility of Religious Education as a Practical Metaphysics - Süleyman Gümüş (Darulfunun Ilahiyat)
While the science of religious education was established in the 19th century in the West, its more recent history commenced in Türkiye in the 1980s. Though the science of religious education has a close connection with religious sciences due to being the education of the Islamic religion in practice, it originally falls under the category of human sciences and takes its scientific principle from educational sciences. The purpose of this study is to discuss the possibility and conditions of reforming the science of religious education, which characterized by its pedagogical nature, into a practical metaphysics. Practical metaphysics unifies all discourses and non-discursive formations that arise from humanity’s pursuit of meaning by focusing on the modality of subject as its topic of research. How the Islamic intellectual tradition divides sciences into two categories (i.e., the traditional and the rational sciences), the weakness of the link between sciences and institutionalization, and even fiqh’s limited interest in ethics and politics despite being a practical science show how important having a scientific discourse about the general image of subjectivity in a sociality is. In addition, religious education as a practical metaphysics can play a crucial role in this context by exploring both the discursive and nondiscursive conditions of this concept, ultimately revealing the unity of this image. The study is based on a document analysis and consists of two sections. The first section provides a critical assessment of religious pedagogy, while the second section elucidates the general characteristics of religious education as a practical metaphysics, which proposes a profound transformation in the meaning of education by addressing the inadequately studied relationship among the natural sciences, the human sciences, and the religious sciences and by addressing educational activities within the structural nature of the historical image of human beings.